FULLY REMOVABLE DENTAL PROSTHESES - Nazhmiddinov Bohodirjon Bahritdin ugli (Galaxy International Interdisciplinary Research Journal, 2021)
Over the decades of existence, prostheses have undergone significant changes both in terms of design and in the materials used for their manufacture. The latest generation of prosthetics is characterized by maximum realism, functionality, and convenient positioning in the oral cavity. They do not interfere with the patient's enjoyment of the taste of food and speak without speech defects, are not visible to others, can be easily adjusted and removed if necessary.